Impact of Plasmodium falciparum infection on DNA methylation of circulating immune cells - Almojil, Dareen; Diawara, Aïssatou; Soulama, Issiaka; Dieng, Mame Massar; Manikandan, Vinu; Sermé, Samuel S.; Sombié, Salif; Diarra, Amidou; Barry, Aissata; Coulibaly, Sam Aboubacar; Sirima, Sodiomon B.; Idaghdour, Youssef (Frontiers in Genetics, 2023)
The regulation of immune cell responses to infection is a complex process that involves various molecular mechanisms, including epigenetic regulation. DNA methylation has been shown to play central roles in regulating gene expression and modulating cell response during infection. However, the nature and extent to which DNA methylation is involved in the host immune response in human malaria remains unknown. Here, we present a longitudinal study investigating the temporal dynamics of genome-wide in vivo DNA methylation profiles using 189 MethylationEPIC 850K profiles from 66 children in Burkina Faso, West Africa, sampled three times: before infection, during symptomatic parasitemia, and after malaria treatment. The results revealed major changes in the DNA methylation profiles of children in response to both Plasmodium falciparum infection and malaria treatment, with widespread hypomethylation of CpGs upon infection (82% of 6.8K differentially methylated regions). We document a remarkable reversal of CpG methylation profiles upon treatment to pre-infection states. These changes implicate divergence in core immune processes, including the regulation of lymphocyte, neutrophil, and myeloid leukocyte function. Integrative DNA methylation-mRNA analysis of a top differentially methylated region overlapping the pro-inflammatory gene TNF implicates DNA methylation of TNF cis regulatory elements in the molecular mechanisms of TNF regulation in human malaria. Our results highlight a central role of epigenetic regulation in mounting the host immune response to Plasmodium falciparum infection and in response to malaria treatment.